DEFORMATION CHARACTERISTICS OF CHOPPED FIBRE COMPOSITES SUBJECTED TO QUASI-STATIC TENSILE LOADING - Jan Šleichrt; Marcel Adorna; Michaela Neühauserová; Nela Fenclová; Veronika Petráňová (Acta Polytechnica CTU Proceedings)
This work presents deformation behaviour of cost effective chopped fiber composites. Use of chopped fibre is advantageous for manufacturing however complex shape parts production technology could be challenging. Batches of samples with different fibres composition were subjected to uni-axial tensile loading to obtain overall materials properties and inspection of proper manufacturing based on local deformation inhomogeneities. Both crossbeam displacement and optical strain measurement were used for elastic characteristics evaluation. Deformation response was derived from full-field optical strain measurements based on digital image correlation method. Relatively large variation of mechanical properties testing of samples was found.